Chemo-kinematics of the Milky Way from the SDSS-III MARVELS survey. Issue 3 (6th September 2018) - Grieves, N; Ge, J; Thomas, N; Willis, K; Ma, B; Lorenzo-Oliveira, D; Queiroz, A B A; Ghezzi, L; Chiappini, C; Anders, F; Dutra-Ferreira, L; Porto de Mello, G F; et al.
ABSTRACT: Combining stellar atmospheric parameters, such as effective temperature, surface gravity, and metallicity, with barycentric radial velocity data provides insight into the chemo-dynamics of the Milky Way and our local Galactic environment. We analyse 3075 stars with spectroscopic data from the Sloan Digital Sky Survey III MARVELS radial velocity survey and present atmospheric parameters for 2343 dwarf stars using the spectral indices method, a modified version of the equivalent width method. We present barycentric radial velocities for a sample of 2610 stars with a median uncertainty of 0.3 km s −1 . We determine stellar ages using two independent methods and calculate ages for 2335 stars with a maximum-likelihood isochronal age-dating method and for 2194 stars with a Bayesian age-dating method. Using previously published parallax data, we compute Galactic orbits and space velocities for 2504 stars to explore stellar populations based on kinematic and age parameters. This study combines good ages and exquisite velocities to explore local chemo-kinematics of the Milky Way, which complements many of the recent studies of giant stars with the APOGEE survey, and we find our results to be in agreement with current chemo-dynamical models of the Milky Way. Particularly, we find from our metallicity distributions and velocity–age relations of a kinematically defined thin disc that the metal-rich end has stars of all ages, even after we clean the sample of highly eccentric stars, suggesting that radial migration plays a key role in the metallicity scatter of the thin disc. All stellar parameters and kinematic data derived in this work are catalogued and published online in machine-readable form.